Is dose-dependent response to bacillus Calmette-Guérin treatment in urothelial carcinoma? - Racca, Fabricio; Morales-Barrera, Rafael; Carles, Joan (Translational Cancer Research; Vol 6, Supplement 1 (February 28, 2017): Translational Cancer Research, 2017)
Bacillus Calmette-Guérin (BCG) intravesical instillation therapy has been established as a standard of care treatment for high-risk non-muscle invasive urothelial carcinoma (NMIUC). To date, many clinical have demonstrated a direct antitumor activity, prevention of tumor recurrence, reductions in tumor progression and, consequently, tumor specific mortality and improvement in overall survival. Nevertheless, the local adverse events arising from BCG intravesical account for about one-third of treatment discontinuations. Strategies to minimize the side effects are needed.